2011
DOI: 10.1209/0295-5075/93/47003
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy investigation of the electronic structure of superconducting FeSe x single crystals

Abstract: X-ray absorption spectroscopy (XAS) Fe K-edge spectra of the FeSe x (x=1-0.8) single crystals cleaved in situ in vacuum reveal characteristic Fe 4sp states, a lattice distortion and the Se K-edge spectra point to a strong Fe 3d-Se 4p hybridization giving rise to itinerant charge carriers. A formal charge of ~1.8+ for Fe and ~2.2-for Se were evaluated from these spectra in the FeSe x (x=0.88). The charge balance between Fe and Se is assigned itinerant electrons located in the Fe-Se hybridization bond. As x decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
4
14
2
Order By: Relevance
“…Therefore, an oxygen incorporated NSC-FeSe film does not have iron in a mostly Fe 3+ state. Our observations of the spectra from minimally exposed FeSe films and oxygen incorporated FeSe films are in agreement with the results from bulk FeSe studied by Yang et al 30 and Chen et al 31 , as well as with theoretical calculations by Lee et al 32 It is concluded that while the same general trend in Fe valence change is observed in both FeTe and FeSe films, the rate at which these occur are different.…”
Section: 21supporting
confidence: 92%
“…Therefore, an oxygen incorporated NSC-FeSe film does not have iron in a mostly Fe 3+ state. Our observations of the spectra from minimally exposed FeSe films and oxygen incorporated FeSe films are in agreement with the results from bulk FeSe studied by Yang et al 30 and Chen et al 31 , as well as with theoretical calculations by Lee et al 32 It is concluded that while the same general trend in Fe valence change is observed in both FeTe and FeSe films, the rate at which these occur are different.…”
Section: 21supporting
confidence: 92%
“…15 By extrapolating the maximum absorption jumps of Se (∼ 12659.2 eV) and SeO 2 (∼ 12662 eV), 14 we estimate ∼ -1.98 for the Se valence, consistent with the formal value of Se ion (2-). For the Fe site, the nearest neighbors are four Se atoms (1×Se(I), 2×Se(II) and 1×Se(III)) with four different distances close to ∼ 2.418Å and the next nearest neighbors are three Fe atoms with almost the same distance (∼ 2.723Å).…”
Section: 13supporting
confidence: 66%
“…Interestingly, the absorption edge signal strengthens in intensity on proceeding from LaCuOSe to LaCuOSe 0.2 Te 0.8 . This trend runs counter to expectations based on decreasing Se concentration, as has been seen, for instance, in Se K-edge spectra for FeSe 1−x Te x , where strong chalcogen-chalcogen bonds (∼2.7Å) are present [40][41][42]. Although absorption spectra measured in fluorescence mode commonly suffer from self-absorption effects, we consider such effects to be unlikely here because the X-ray energy is quite high (12 keV), which reduces photoionization cross-sections [43], the samples analyzed are thin [44][45][46], and the Se concentrations are low.…”
Section: Xanes Spectracontrasting
confidence: 95%